IMPLEMENTATION OF CONSTITUTIONAL RIGHTS FOR BPJS HEALTH PATIENTS AT REGIONAL GENERAL HOSPITALS (RSUD) SERANG CITY - Sefa Martinesya; Wirda Garizahaq; Fuadi Brylian Yanri; Lizy Marchelina Butarbutar (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2025)
Article 28H paragraph (1) of the 1945 Constitution of the Republic of Indonesia mandates that every person has the right to physical and spiritual prosperity, to a place to live, and to a good and healthy environment, as well as the right to health services, and Article 34 paragraph (3) of the 1945 Constitution of the Republic of Indonesia stipulates that the state is responsible for providing adequate health care facilities and public services. However, the reality on the ground shows that there is still discrimination or unequal treatment of patients based on their payment status, namely General Patients and BPJS Health Patients. Where General Patients, who pay directly for health services, often get faster access, a wider choice of doctors, and priority in the use of facilities and medical procedures. Conversely, BPJS Patients often experience longer waiting times, limited facilities, and complicated bureaucratic procedures. The purpose of this study is to analyze the implementation of constitutional rights for BPJS patients at the Serang City Regional General Hospital (RSUD). This study uses a normative legal research method, with data sources obtained from secondary and primary data, which are then analyzed qualitatively.